Quality and composition of three palm oils isolated by clean and sustainable process - Silva, Claudia Marques da; Zanqui, Ana Beatriz; Visentainer, Jesui Vergilio; Cardozo-Filho, Lucio [UNESP]; Stival Bittencourt, Paulo Rodrigo; Morais, Damila Rodrigues; Santos, Jandyson Machado; Eberlin, Marcos Nogueira; Matsushita, Makoto (Elsevier B.V., 2020)
Protocols that employ environmentally friendly solvents for lipid extraction are promising. The objective of this research was to apply subcritical extraction to three species of palm mesocarp in order to compare their compositions and the effectiveness of the environmentally correct extraction protocol to obtain oil free of toxic residues. Subcritical fluid extraction (SubFE) was employed to extract lipids from Elaeis guineensis Jacq., Elaeis oleifera (Kunth) Cortes, and Elaeis guineensis x Elaeis oleifera, using as solvent n-propane and ethanol. The composition of fatty acids, acylglycerols, carotenoids, antioxidant capacity, and thermogravimetric behavior were evaluated in the oils obtained by SubFE, Soxhlet (SE) and Bligh and Dyer (BD) extraction protocols. The extraction yield varied according to the palm oil species and the extraction method, the highest yield was 73.97% for African palm using SubFE. The total carotenoids content extracted by SubFE was higher for all palm species used in this work than that obtained by Soxhlet extraction. The different extraction methods did not influence the fatty acid profile, and the results indicated a high content of omega-9 and omega-6 fatty acids. Therefore, SubFE is a promising extraction protocol for obtaining palm oil, using environmentally friendly solvents, which allows extracting oils of similar composition to those extracted by conventional methods. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Subcritical fluid extraction; Antioxidant capacity; Fatty acids; Palm oil; Total carotenoids